INTERNET FINANCIAL REPORTING: A SYSTEMATIC LITERATURE REVIEW - Muhammad Hamdan Sayadi; Falikhatun (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to develop a study of specific features by examining current developments in online reporting. This is important to improve researchers' understanding of the development of the topic